DESIGN OPTIMIZATION AND STATISTICAL ANALYSIS OF TRAINER AIRCRAFT WING STRUCTURE TO PREDICT FATIGUE LIFE - SITARAM PRASAD, VEERAVALLI; UPENDER, VENGALA; SATISH REDDY, BOMMU; NAVEEN, E. (International Journal of Psychosocial Rehabilitation, 2019)
As part of this inquiry, the wing structure of a training aircraft was thoroughly designed using a CATIA project. After that, a stress study of the wing structure is performed to ascertain the stresses being applied to it. The finite element method is utilized to forecast the stresses in order to calculate the safety factor of the structure with the help of ANSYS. In a construction such as an airplane, a fatigue fracture can happen where the most tensile stress is applied. For life prediction, three things are needed: a model for the accumulation of fatigue damage; constant amplitude S-N (stress life) data throughout a range of stress ratios; and local stress history at the stress concentration. A structural response analysis of the wing is planned. This particular study looks at the trainer aircraft's wing structure, specifically the skin, spars, and ribs. The wing is made up of fifteen ribs and two spars covered in skin. The front spar has an "I" section and the back spar a "C" shape. To find the strains that the imposed pressure load will cause on the spars and ribs, a stress and fatigue assessment of the entire wing section must be finished. The following are potential search terms: fatigue life prediction, static analysis, CATIA, Ansys, and aircraft wing.